Pengembangan Media Pembelajaran INKA (Ide Nasihat Kreativitas Anekdot) pada Materi Teks Anekdot Siswa Kelas X SMA Negeri 2 Tanjungpinang Tahun Pelajaran 2023/2024: Pengembangan Media Pembelajaran INKA (Ide Nasihat Kreativitas Anekdot) pada Materi Teks Anekdot Siswa Kelas X SMA Negeri 2 Tanjungpinang Tahun Pelajaran 2023/2024 - Inka Puspita Ningrum; Isnaini Leo Shanty; Siti Habiba (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This research has the aim of developing learning media ideas anecdote creativity advice (INKA) on anecdote text material for grade X high school students Negeri 2 Tanjungpinang in the 2023/2024 school year. This research uses the 4D model until the development stage. The product developed is in the form of visual learning media with impraboard as the base material. Media his learning media has been assessed by two experts, namely media experts and material experts. Trial test this media trial was conducted on two groups of students, namely 6 students for small groups and 40 students for large groups. Data collection techniques in this study, namely interviews, media validation questionnaires by media experts and material experts, as well as questionnaires of media practicality by students. Data analysis techniques in this study were carried out with two techniques, namely descriptive qualitative and descriptive quantitative. Media expert validation got an average of 95% with the qualification of